Analysis of issues controlling the feasibility of automobile remanufacturing business in India. (2017) - Sinha, Ajay; Mondal, Sandeep; Boone, Tonya; Ganeshan, Ram
In the last three decades, remanufacturing has grown into a significant business sector in developed countries. Take-back obligations, disposal bans, economic benefits, creation of stock of components/parts from disassembly and demand for spare parts during post product life cycle period are key enablers of growth for this business sector. In India, the remanufacturing business is mostly practiced as a disorganised sector. Though Indian automobile industry holds the tenth position in the entire world, second in two wheelers and fourth in commercial vehicles, there are no significant initiatives either from the government or from the industry to pursue remanufacturing as a separate business entity. This paper presents an empirical investigation of the Indian automobile industry and explores the reasons behind the slow growth of remanufacturing as a profitable business option. The survey identifies critical issues that impact the feasibility of automobile remanufacturing in India. It also identifies the differences in perception on remanufacturing by different players in the automobile supply chain, that is, heavy commercial vehicles (HCVs), light commercial vehicles (LCVs), car, two wheeler or original equipment manufacturers (OEMs) and suppliers.